Suržyk u svitli Teoriji movnogo standartu Dalibora Brozovića - Fuderer, Tetyana (Array, 2008)
Different aspects of observations and a variety of positions of linguists in the research of surzhyk resulted in the appearance of a number of interdisciplinary terms for denoting the same linguistic phenomenon (Stavytska, Trub 2007:31-120), although until today in the Ukrainian language science there is no generally accepted definition of the concept outlined by the terminolexeme surzhyk. The main objective of the article is to analyse surzhyk by applying the Theory of language standard developed by Croatian linguist D. Brozović and to provide own definition of this sociolinguistic phenomenon in the context of the above mentioned Theory.